2011
DOI: 10.4103/1817-1737.74273
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for bronchiectasis: The effect of morphological types to prognosis

Abstract: BACKGROUND:Although the incidence has declined over the past years in societies with high socioeconomic status, bronchiectasis is still an important health problem in our country.AIM:To review and present our cases undergoing surgery for bronchiectasis in the past 12 years and their early and late term postoperative outcomes and our experience in bronchiectasis surgery and the effect of morphological type on the prognosis.METHODS:The medical records of 62 cases undergoing surgical resection for bronchiectasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
3
17
0
1
Order By: Relevance
“…In previous studies, this ratio ranged between 64.7% and 90.7%. [ 3 , 5 , 11 - 14 , 31 , 32 ] In the patients who underwent complete resections, we found that 58.9% were asymptomatic, 33.3% showed an improvement, and 0.9% showed a deterioration, consistent with the literature. If a complete resection cannot be done due to excessive bronchiectasis and medical treatment is inadequate in life-threatening hemoptysis or infection-related complications which affect the patient"s daily routine, a palliative resection (incomplete resection) can be done by removing the areas most affected to relive the symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…In previous studies, this ratio ranged between 64.7% and 90.7%. [ 3 , 5 , 11 - 14 , 31 , 32 ] In the patients who underwent complete resections, we found that 58.9% were asymptomatic, 33.3% showed an improvement, and 0.9% showed a deterioration, consistent with the literature. If a complete resection cannot be done due to excessive bronchiectasis and medical treatment is inadequate in life-threatening hemoptysis or infection-related complications which affect the patient"s daily routine, a palliative resection (incomplete resection) can be done by removing the areas most affected to relive the symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…The predominant lesion could be determined reliably on preoperative CT scan because the degree of bronchiectatic radiological abnormality was associated commonly with clinical manifestation and the patient's quality of life. [24][25][26][27] Therefore, a marked symptomatic improvement and a good satisfactory outcome could be obtained in nonlocalized bronchiectatic patients after removal of the predominant lesion, as shown in our study. It is worth mentioning that the surgical benefit is limited to patients who have only one predominant area of bronchiectatic disease that can be localized by CT, instead of those with diffuse bronchiectasis (ie, cystic fibrosis).…”
Section: Discussionsupporting
confidence: 81%
“…25 Etiology of bronchiectasis was attributed to non-tuberculosis infection if bacterial or viral infections were well documented in the medical records. 26 The diagnosis of CF was based on at least two of the following criteria: sweat chloride concentration >60 mEq/mL, two clinical features consistent with CF, or genetic testing demonstrating two mutations associated with CF. 27 The diagnosis of PCD was made clinically and confirmed through transmission electron microscopy.…”
Section: Patientsmentioning
confidence: 99%